Effect of phytase on the bioavailability of phosphorus of rice bran in broilers chickens - Conte, Ademir José; Teixeira, Antonio Soares; Figueirêdo, Agostinho Valente de; Vitti, Dorinha Miriam Silber Schmidt; Filho, José Cleto da Silva (Pesquisa Agropecuaria Brasileira, 2002)
This work has intended to determine the action of phytase on the bioavailability of phosphorus of rice bran in the diet for broiler chickens through the isotopic dilution technique. The treatments consisted of a diet based on corn and soybean meal, without supplementation of inorganic phosphorus (0.388% of total P) and four diets of 15% of whole rice bran without supplementation of inorganic phosphorus (0.56% of total P) with four levels of phytase (0, 400, 800 and 1,200 FTU/kg). On the fifth day of the experiment, each bird was given, peritoneal via, 3.5 MBq of 32P. On the four subsequent days, blood and excreta samples were collected for further analyses. The fecal endogenous losses, plasma apparent and true absorption of phosphorus increased in a significant manner (P < 0.01) with the use of growing levels of phytase in the diet. The bioavailability of phosphorus was of 38.06% in the diet with rice bran and without enzyme and increased to 51.54%, 61.31% and 59.54% using 400, 800 and 1,200 FTU/kg, respectively. Through quadratic regression the point of maximum bioavailability of 60.8% was determined with the use of 982 FTU/kg. Phosphorus bioavailability of rice bran, determined by splitting, was of 28.1% and raised in a linear form (P < 0.05) to 38.3%, 50.2% and 54% with the use of 400, 800 and 1,200 FTU/kg.